Industrial Diversification and Shareholders' Value in China: The Case of Shanghai Listed Manucfaturing Firms - von Eije, Henk; Jin, Jiong (UI Scholars Hub, 2009)
The fast growing economy and institutional and economic reforms made the Chinese equity markets the third largest in Asia. This leads to strategies of industrial diversification within Chinese firms. Financial theory suggests that industrial diversification may have advantages in emerging markets, because conglomerates are better able to cope with market imperfections than focused firms. Moreover, diversification through investing in many shares may be costly in imperfect markets. Negative effects of diversification can be found if hubris generates too large take-over premiums or if managers consume perks related to company size. Also, tunneling and propping may reduce company value. We show that Chinese diversified firms are underperforming in comparison to focused firms. The potential positive effects of industrial diversification are thus smaller than the negative effects. Besides the aforementioned aspects, myopic shareholders, management history, and inadequate regulation of shareholders' interst may have contributed to the current negative diversification effects in China.